A review of recently developed polymer composite materials for fused deposition modeling 3D printing. (15th December 2021) - Dewada, Surendra Singh; Telang, Amit
Abstract: Additive Manufacturing (AM) is a rapidly evolving technology due to its numerous advantages over traditional manufacturing processes. AM processable materials are limited and have poor mechanical performance, restraining the technology's potential for functional part manufacturing. Although FDM is the most popular and growing technique, the inferiority of the material limits its application to prototyping. Nanocomposite material improves the thermal, mechanical, and electrical performance of FDM objects. Mostly polymer nanocomposites are feasible to process and several researchers have reported enhanced performance with polymer nanocomposites. Carbon nanotubes, graphene nanoplatelets, nano clay, and carbon fiber are primary reinforcements to thermoplastics. The current state of the art relevant to advances in nanocomposites for the FDM process, as well as the influence of nanofillers on mechanical properties of the build object are reviewed in this paper.